The Influence of the “Dine Out Deals” Discount Promotion and Visual Communication Design on Consumer Purchase Decisions in GrabFood Services at Sun Plaza Mall Medan with Purchase Intention as a Mediating Variable - Dian Natari; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (Journal of Business Management, 2025)
The lower transaction value of GrabFood compared to its competitors raises questions about market dominance and the sustainability of the platform's growth. Visual communication design should help convey information, but the effectiveness of the "Dine Out Deals" visual promotion strategy at GrabFood Sun Plaza Medan is questionable because many consumers are unaware of the promotion, even though they have seen the material. This study aims to analyze the direct and indirect effects of the "Dine Out Deals" discount promotion and visual communication design on purchasing decisions for GrabFood services at Sun Plaza, with purchase interest as a mediating variable. This is an associative study using primary and secondary data. The population consists of all GrabFood users at that location. The sampling technique used was nonprobability sampling with a purposive sampling approach. The data analysis method is SEM-PLS. The variables consist of two independent variables, one mediating variable, and one dependent variable. The instrument contains 21 statements. Hair's minimum sample size rule is 21x8=168, and this study involved 168 respondents. Data collection was conducted through questionnaires administered to GrabFood users at Sun Plaza Medan. The results show that: (1) the "Dine Out Deals" discount promotion and visual communication design have a significant direct effect on purchase interest; (2) the "Dine Out Deals" discount promotion has a significant indirect effect on purchase decisions; (3) visual communication design has a significant direct effect on purchase decisions; (4) purchase intention has a significant indirect effect on purchase decision; (5) the "Dine Out Deals" promotion has an indirect effect on purchase decision through purchase intention; (6) visual communication design has an indirect effect on purchase decision through purchase intention.